Academic Senate Minutes 2010-03-11 - Academic Senate:::::::::
Chair Report. Approval of Agenda. Minutes of 2/25/10 approved. MSCES curriculum revision – approved. Solano Program – approved. President Report. Provost Report. Update of FSAC portion of the By-Laws approved. Vice President of Administration and Finance Report. Vice President of SAEM Report. Associated Students Report. Periodic Review of Temporary Faculty Policy – First Reading. Resolution Opposing Expansion of WalMart in Rohnert Park – approved. Arts and Humanities GE reform proposal – First Reading. CFA Report. Chair-Elect Report. APC Report. EPC Report. FSAC Report.